Managing Muslim funeral reporting using E-Easy Funeral with utilization of instant messaging / Nor Izzat Shazwan Anuar and Siti Zulaiha Ahmad - Anuar, Nor Izzat Shazwan; Ahmad, Siti Zulaiha (Universiti Teknologi MARA, Perlis, 2023)
Managing the funeral process among Muslims usually depends on the mosque committee's competency to inform the family of the deceased. Various problems have been faced by users when reporting death case funeral arrangements such as the lack of a specific platform for them to create a death report. Currently, users need to make a phone call or send a Short Message System (SMS) to report the case to the committee. This has made it difficult for the committee to manage the funeral arrangements as the information was not received or communicated clearly. Therefore, this study introduces a simplified approach to funeral reporting application using a mobile platform integrates with instant messaging services to assist users in making death reports to the committee for funeral management known as EEasy Funeral. This study simplifies and adapts the Waterfall Model phases into a 3-phases development model, which are analysis and design, development, and evaluation. E-Easy Funeral targets Muslim communities and mosque committees that manage the funeral process. Hence, this study conducted usability testing and user acceptance testing to measure the usability and the acceptability of E-Easy Funeral among the targeted users (46 participants) using the usability test instrument and the Technology Acceptance Model instrument. As the result, based on the average means core of the three dimensions of the usability test and the four dimensions of the User Acceptance Test, clearly shows that the E-Easy Funeral application is usable and positively accepted by the users. Having considered the evaluation results and the responses by the participants, this study has successfully introduced a simplified and user-friendly mobile application for a funeral reporting tool to inform death cases for funeral management.